1993
DOI: 10.1021/ic00070a011
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of autoxidation of cobalt(II) cyclidene dioxygen carriers

Abstract: The cobalt(II) cyclidene complexes are known to bind dioxygen reversibly under ambient conditions; however, the lifetime of the dioxygen adduct is limited by autoxidation. This paper describes a study of the autoxidation reactions of the cobalt(II) cyclidenes in nonaqueous media. The kinetics of the autoxidation reaction of the cobalt(II) complex are dependent on the nature of the ligand substituents and dioxygen concentration and on the nature and concentration of added base. Mechanistic details have been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Autoxidation. Previous studies on the kinetics and mechanism of autoxidation of cobalt(II) cyclidene−dioxygen adduct , revealed a conjugate base mechanism in which deprotonation may occur either in the rate determining step or in a preequilibrium step. In previous studies, substitution for relatively acidic protons at the R 2 and R 3 positions had given orders or magnitude decreases in rates of autoxidation, but the same conjugate mechanism persisted, albeit at much retarded rates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Autoxidation. Previous studies on the kinetics and mechanism of autoxidation of cobalt(II) cyclidene−dioxygen adduct , revealed a conjugate base mechanism in which deprotonation may occur either in the rate determining step or in a preequilibrium step. In previous studies, substitution for relatively acidic protons at the R 2 and R 3 positions had given orders or magnitude decreases in rates of autoxidation, but the same conjugate mechanism persisted, albeit at much retarded rates.…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the R 3 methyl group by phenyl results in a 20-fold retardation of the rate of autoxidation. However, the complexes do still undergo autoxidation, and the rates respond to base in a manner suggestive of the conjugate base mechanism . The methyl groups at the R 4 positions are common to all structures and the most likely sites for deprotonation in those cases where NH and ionizable R 3 groups have been eliminated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of those reactions are known (32)(33)(34) and are initiated by protons contained in the solvent (Scheme 7, (12) and (13)), by the solvent itself (Scheme 7, (14)) or by autooxidation of the adduct (Scheme 7, (15) and (16)) (34). The first studies initiated by our industrial partner (5,6), showed that when no oxygenated complex remained in solution, the ligand would still be intact.…”
Section: Half Lifetimesmentioning
confidence: 99%
“…These totally synthetic materials provide an almost ideal environment for dioxygen binding to the central atoms, with an additional advantage in the ease with which structural modifications may be carried out on the ligand. This, in turn, allows systematic studies of the effect of structural modifications on dioxygen affinities, rates of binding, dissociation, and autoxidation, and relative efficacies of different conformers.
1 Planar (a) and three-dimensional (b) representations of cyclidene complexes. These complexes are denoted below as M(R 1 R 2 R 3 R 4 cyclidene), where M = Ni or Co.
…”
Section: Introductionmentioning
confidence: 99%